Idempotent and compact matrices on linear lattices: a survey of some lattice results and related solutions of finite relational equations - Fortunata Liguori; Giulia Martini; Salvatore Sessa (International Journal of Mathematics and Mathematical Sciences)
After a survey of some known lattice results, we determine the greatest idempotent (resp. compact) solution, when it exists, of a finite square rational equation assigned over a linear lattice. Similar considerations are presented for composite relational equations.